The Students’ Obstacles on Paraphrasing Skills: Array - Dede Nurdiawati (Fakultas Keguruan dan Ilmu Pendidikan Universitas Peradaban, 2018)
Abstract: One of the main problems faced by students learning English as a second language is their inability to paraphrase passages. The objective of the paper is to find out the obstacles that students faced in paraphrasing skills. The method of the research used is a descriptive qualitative study in which the data are taken from interview. To determine the sample, the writer uses purposive sampling technique. The number of the research subject is 31 students as respondents. The samples are then given post-task interview to get the supporting data on their basic understanding on paraphrasing as well as their self-acknowledgement about their obstacles in paraphrasing. The result of the research shows that there are several obstacles such as limited vocabulary mastery (48.38%), lack of ability in catching the content of the original text (29.03%), lack of ability in re-arranging the sentence structure (16.12%), lack of experience in conducting paraphrasing (3.22%), and lack of ability in putting citation properly (3.22%). It shows problem solving to overcome the obstacles of the students’ paraphrasing ability, such as; give a clear understanding about the difference between paraphrasing and summarizing; intensive activity requiring the students to conduct paraphrasing; learn and improve in catching the content of the text, and also pay attention to enrich the vocabulary mastery.